THE ANTI-AVOIDANCE PROTECTION OF EUROPEAN UNION FINANCIAL TRANSACTION TAX - Gruodis, Povilas (Teisė, 2015)
In this Article is analyzed financial transaction tax projects proposed by the European Commission in 2011 and 2013. The article focuses on the proposed regulation of the object and the jurisdiction of the financial transaction tax. The proposed regulation of the financial transaction tax is analyzed concerning possible threats of the new taxation related with tax avoidance. In this article the analysis of the proposed regulation was done reviewing the main arguments of the opponents of the financial transaction tax. The analysis of the proposed financial transaction tax projects leads to conclusion that the chosen regulation of the object of the financial transaction tax when the tax object is defined through two separate elements (financial transaction and financial security) is effective and comprehensive – the new regulation is safe enough against possible cases of tax avoidance. Also the analysis of the proposed financial transaction tax projects leads to conclusion that the proposed regulation of the financial transaction tax jurisdiction is based on the two separate principles (counterparty principle and issuance principle). This new and innovative legal construction fully prevents possible tax avoidance issues related with changing the jurisdiction of the taxable financial activities.